A panel of three serum microRNA can be used as potential diagnostic biomarkers for nasopharyngeal carcinoma. Issue 2 (14th January 2022) - Li, Rongkang; Lu, Chong; Yang, Weiqiang; Zhou, Yaqi; Zhong, Jiatao; Chen, Xuan; Li, Xinji; Huang, Guocheng; Peng, Xiqi; Liu, Kaihao; Zhang, Chunduo; Hu, Hongyi; et al.
Abstract: Background: Nasopharyngeal carcinoma is cancer with unique epidemiological characteristics, showing obvious ethnicity, gender, and geographical prevalence. More and more evidence shows that microRNAs are stable in serum and are specific to different tumor types. Therefore, miRNA is a new non‐invasive biomarker for cancer detection. Methods: The experiment is divided into three stages, namely, the screening stage, the training stage, and the verification stage. We took 54 patients with nasopharyngeal carcinoma and 108 healthy controls as the research objects. We use the receiver‐operating characteristic (ROC) curve and area under the ROC curve (AUC) to evaluate the diagnostic value of miRNA. Finally, a three‐miRNA panel with high diagnostic efficiency was constructed. In addition, we conducted biological information analysis of these miRNAs to explore their functions. Results: In NPC patients, the expression of five serum miRNAs (miR‐29c‐3p, miR‐143‐5p, miR‐150‐5p, miR‐145‐3p, and miR‐205‐5p) is significantly dysregulated. Among them, the diagnostic value of these three miRNAs (miR‐29c‐3p, AUC = 0.702; miR‐143‐5p, AUC = 0.733; and miR‐205‐5p, AUC = 787) is more prominent. The diagnostic panel constructed by them has a higher diagnostic value (AUC = 0.902). Through the analysis of the TCGA data set, the target gene of the three‐miRNA panel may be KLF7, NRG1, SH3BGRL2, and SYNPO2. Conclusion: The three‐miRNA panel (miR‐29c‐3p, miR‐143‐5p, and miR‐205‐5p) may become a novel non‐invasive biological marker for nasopharyngeal cancer screening. Abstract : Our study showed that a panel of three serum microRNAs may be performed as a novel and non‐invasive biomarker to diagnose nasopharyngeal carcinoma, with AUC = 0.902. And the development of nasopharyngeal carcinoma may relate to the three‐miRNA panel, the further study was needed to do.